Rynkatorpa felderi, new species, from a bathyal hydrocarbon seep in the northern Gulf of Mexico (Echinodermata: Holothuroidea: Apodida) - Pawson, David L.; Vance, Doris J. (Zootaxa, 2005)
Rynkatorpa felderi new species was collected at a cold hydrocarbon seep at bathyal depths in the northern Gulf of Mexico. This is the first record of a synaptid holothurian from a chemosynthetic site, and the first record of the genus Rynkatorpa in the Atlantic; all other congeners are known from the Indo-Pacific.